2023
DOI: 10.1111/dom.15229
|View full text |Cite
|
Sign up to set email alerts
|

Labisia pumila standardized extract (SKF7®) reduces percentage of waist circumference and waist‐to‐height ratio in individuals with obesity

Abstract: AimEvidence from the literature points towards a viable choice of utilizing Labisia pumila to improve the metabolic profile in animal studies. To that end, this prospective study was designed to assess the health impact of the consumption of L. pumila standardized extract (SKF7®) on key parameters of obesity in humans such as body weight (BW), body mass index (BMI), waist circumference (WC) and waist‐to‐height ratio (WHtR).Materials and MethodsA dose‐ranging analysis using SKF7® was conducted through a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Consequently, there has been a substantial increase in the utilization of complementary and alternative medicines as either a substitute for or adjunct to conventional pharmaceutical interventions within human society over the preceding decades. 10.11113/mjfas.v20n2.3369 Fortunately, several naturally occurring substances exhibit anti-inflammatory properties. For instance, it has been observed that omega-3 fatty acids possess the ability to impede the activity of pro-inflammatory molecules, including eicosanoids, cytokines, and reactive oxygen species (ROS) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there has been a substantial increase in the utilization of complementary and alternative medicines as either a substitute for or adjunct to conventional pharmaceutical interventions within human society over the preceding decades. 10.11113/mjfas.v20n2.3369 Fortunately, several naturally occurring substances exhibit anti-inflammatory properties. For instance, it has been observed that omega-3 fatty acids possess the ability to impede the activity of pro-inflammatory molecules, including eicosanoids, cytokines, and reactive oxygen species (ROS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Labisia pumila var alata, popularly known as "Kacip Fatimah," has a long history of use by Malaysian women to facilitate childbirth and treat postpartum problems and is hence renowned as the "queen of plants" among Malaysian medicinal plants [8,9]. L. pumila extract is rich in polyphenolic chemicals with anticancer and weight management benefits [10]. L. pumila's value as a disease preventative is mostly attributable to its phytoestrogen, anti-inflammatory, and antioxidant properties [11,12].…”
Section: Introductionmentioning
confidence: 99%